EFFECTIVENESS OF AI-INTEGRATED COLLABORATIVE WRITING AMONG UNIVERSITY EFL STUDENTS IN WRITING FLUENCY - M. Fadhly Farhy Abbas; Vina Fathira; Satria Adi Pradana (English Review: Journal of English Education, 2026)
This research aims to investigate the effectiveness of AI-integrated collaborative writing on writing fluency of EFL students in higher education. The method employed was quantitative with quasi- experimental design. There were 40 students divided into experimental and control groups. Technique of collecting data was writing tests before and after the treatment. The technique of analyzing data used paired sample t-tests and independent sample t-tests for determining writing ability and comparisons between groups. The results showed that both groups experienced improvements in writing ability, but the experimental group using AI integration showed a more significant improvement. These findings revealed that the use of AI, such as ChatGPT, QuillBot, Grammarly, and DeepL, can act as a digital scaffold that helps students develop ideas, improve grammar, and increase writing fluency more effectively. Practically, this study provides evidence that AI integration in collaborative learning can improve quality and efficiency of writing learning process in higher education. The findings also suggest that combining technological tools with collaborative strategies creates a more supportive and interactive learning environment for EFL students. Therefore, AI-integrated collaborative writing can be considered an innovative pedagogical approach to enhance writing fluency in higher education contexts.